Functional analyses of mitoribosome 54S subunit devoid of mitochondria‐specific protein sequences. Issue 3 (10th November 2021) - Santos, Barbara; Zeng, Rui; Jorge, Sasa F.; Ferreira‐Junior, Jose Ribamar; Barrientos, Antoni; Barros, Mario H.
Abstract: In Saccharomyces cerevisiae, mitoribosomes are composed of a 54S large subunit (mtLSU) and a 37S small subunit (mtSSU). The two subunits altogether contain 73 mitoribosome proteins (MRPs) and two ribosomal RNAs (rRNAs). Although mitoribosomes preserve some similarities with their bacterial counterparts, they have significantly diverged by acquiring new proteins, protein extensions, and new RNA segments, adapting the mitoribosome to the synthesis of highly hydrophobic membrane proteins. In this study, we investigated the functional relevance of mitochondria‐specific protein extensions at the C‐terminus (C) or N‐terminus (N) present in 19 proteins of the mtLSU. The studied mitochondria‐specific extensions consist of long tails and loops extending from globular domains that mainly interact with mitochondria‐specific proteins and 21S rRNA moieties extensions. The expression of variants devoid of extensions in uL4 (C), uL5 (N), uL13 (N), uL13 (C), uL16 (C), bL17 (N), bL17 (C), bL21 (24), uL22 (N), uL23 (N), uL23 (C), uL24 (C), bL27 (C), bL28 (N), bL28 (C), uL29 (N), uL29 (C), uL30 (C), bL31 (C), and bL32 (C) did not rescue the mitochondrial protein synthesis capacities and respiratory growth of the respective null mutants. On the contrary, the truncated form of the mitoribosome exit tunnel protein uL24 (N) yields a partially functional mitoribosome. Also, the removal of mitochondria‐specific sequences from uL1 (N), uL3 (N), uL16 (N), bL9 (N), bL19 (C), uL29 (C), and bL31 (N) did not affect the mitoribosome function and respiratory growth. The collection of mutants described here provides new means to study and evaluate defective assembly modules in the mitoribosome biogenesis process. Abstract : (A) Structure of the 54S subunit of the mitoribosome. Mitochondria‐specific proteins are coloured in yellow, and those with bacterial homologs are in blue. The 21S rRNA is in grey. (B) The mitochondria‐specific extensions present in the conserved proteins are now coloured in red. The extensions of uL3 (N), uL4 (C), uL5 (C), uL13 (C), bL17 (C), bL19 (C), bL21 (N), uL22 (N), uL22 (C), bL27 (C), and uL30 (N) showed in the panel represent some of the mitochondria‐specific extensions studied in this work. Take away: The functional relevance of mit‐specific extensions of mLSU were evaluated. Seven mit‐specific extensions are not necessary for yeast respiratory growth. Removal of extensions from 14 mtLSU resulted in unfunctional variants.